To simplify the given equation \(2(x−5)=9−3x+6+8+3x+7\), we will start with both sides:
Simplifying the Left Side:
Using the Distributive Property on the left side:
\[ 2(x - 5) = 2x - 10 \]
Simplifying the Right Side:
Next, we'll simplify the right side by combining like terms:
\[ 9 - 3x + 6 + 8 + 3x + 7 \]
First, combine the constant terms \(9 + 6 + 8 + 7\):
\[ 9 + 6 = 15 \ 15 + 8 = 23 \ 23 + 7 = 30 \]
Then, combine the \(x\) terms \(-3x + 3x\):
\[ -3x + 3x = 0 \]
Putting it all together, the right side simplifies to:
\[ 0x + 30 = 30 \]
Summary of Simplifications:
- Left Side Simplified: \(2x - 10\)
- Right Side Simplified: \(30\)
So, the responses are:
- Simplified Left Side: \(2x - 10\)
- Simplified Right Side: \(30\)